Respuesta :
Answer:
x = -3 and y = -2
Step-by-step explanation:
It is given that,
-7x + 6y = 9 ----(1)
-2x - 5y = 16 -------(2)
To find the solution of given equations
eq(1) * 2 ⇒
-14x + 12y = 18 ------(3)
eq(2) * 7 ⇒
-14x - 35y = 112 ---(4)
eq (3) - eq(4) ⇒
-14x + 12y = 18 ------(3)
-14x - 35y = 112 ---(4)
0 4y = -94
y = 94/(-47) = -2
Substitute the value of y in eq (2)
-2x - 5y = 16 -------(2)
-2x - 5*-2 = 16
-2x +10 = 16
-2x = 6
x = 6/-2 = -3
Therefore x = -3 and y = -2
Answer:
[tex]x=-3\\\\y=-2[/tex]
Step-by-step explanation:
Given the system of equations [tex]\left \{ {{-7x+6y=9} \atop {-2x-5y=16}} \right.[/tex], you can use the Elimination Method to solve it.
You can multiply the first equation by -2 and the second equation by 7, then add both equations and solve for the variable "y":
[tex]\left \{ {{14x-12y=-18} \atop {-14x-35y=112}} \right.\\...........................\\-47y=94\\\\y=\frac{94}{-47}\\\\y=-2[/tex]
Substitute the value of "y" into any original equations and solve for the variable "x". Then:
[tex]-7x+6y=9\\\\-7x+6(-2)=9\\\\-7x-12=9\\\\-7x=9+12\\\\x=\frac{21}{-7}\\\\x=-3[/tex]